Evaluating an ABA-Based Early Stimulation Program for Children with Speech Delay in a Resource-Limited Indonesian Kindergarten: A CIPP Model Approach - Sinuhaji, Betaria Br; Pujaningsih, Pujaningsih (Journal of Innovation and Research in Primary Education, 2025)
Speech delay among preschool children increased significantly at TK St. Fransiskus Assisi Sangatta, from 2 cases (2021-2022) to 9 cases (2023-2024). This study evaluated the implementation of an Applied Behavior Analysis (ABA)-based early stimulation program for children with speech delay using the CIPP (Context, Input, Process, Product) model. A qualitative evaluative research was conducted on five children aged 4-5 years who participated in the program for at least one year. Data were collected through structured observations, questionnaires distributed to parents, teachers, and stimulation providers, semi-structured interviews, and analysis of children's developmental documentation. Context evaluation revealed the program aligned with the institution's inclusive needs. Input evaluation exposed resource limitations with only two ABA-trained staff and limited facilities. Process evaluation demonstrated systematic implementation of Discrete Trial Training 3-4 times weekly, despite challenges in attendance consistency and parental involvement. Product evaluation showed all participants achieved significant progress, particularly in receptive language skills, with optimal outcomes in children receiving consistent parental support. The ABA program effectively improved language development in children with speech delay in resource-limited educational settings, but requires enhanced professional training, material support, and structured parental involvement for optimal outcomes.